Ego Defense Mechanism of the Wife with PCOS in the Short Film "Pejuang Garis Dua" by @mteampictures - Putri, Tasya Sukma; Purbani, Widyastuti; Liliani, Else (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2024)
The aim of this research is to know the form of ego defense mechanism of the wife in the Short Film ”Pejuang Garis Dua” by @mteampictures. This kind of research is qualitative descriptive. The researcher collect data sources in the speech of the main character, Zahra, which is in the movie. The researcher do the research phase, which is data collection, data reduction, data analysis, and deduce. In data collection, the researcher watch a movie, doing a speech impediment in the movie, feeding data on speech, and classify data by category. Then, the data is reduced by selecting needed data or discard unnecessary data. The data analysis use ego defense mechanism Sigmund Freud Theory. Next step is the researcher explain the result of descriptive research result. The final step is deduce. The result of this research is the ego defense mechanism present because it growing anxiety resulting from the inability desire in the id. The form of the ego defense mechanism found in the wife is displacement, repression, sublimation, adan rationalization.